Anti-Yo antibodies and cerebellar degeneration in a man with adenocarcinoma of the esophagus. - Sutton, I; Fursdon Davis, C; Esiri, M; Hughes, S; Amyes, E; Vincent, A (2001)
Serum antibodies to the Yo antigen are usually associated with paraneoplastic cerebellar degeneration arising in female patients with gynecological or breast malignancy and are rarely associated with other tumors. We report a male patient who presented with paraneoplastic cerebellar degeneration and anti-Yo antibodies following removal of an esophageal adenocarcinoma. This is only the third report of anti-Yo antibodies occurring in a male patient. The Yo antigen was expressed by the esophageal tumor but not in a frontal lobe cerebral metastasis identified at postmortem. Interestingly, CD8+ T-cell infiltration was also found in the tumor, but not in the metastasis, consistent with down-regulation of Yo expression by the tumor cells leading to evasion from immune-mediated tumor surveillance.